Homeless in America, Homeless in California - Quigley, John M.; Raphael, Steven; Smolensky, Eugene (The Review of Economics and Statistics, 2001)
It is generally believed that the increased incidence of homelessness in the United States has arisen from broad societal factors, such as changes in the institutionalization of the mentally ill, increases in drug addiction and alcohol usage, and so forth. This paper presents a comprehensive test of the alternate hypothesis that variations in homelessness arise from changed circumstances in the housing market and in the income distribution. We assemble essentially all the systematic information available on homelessness in U.S. urban areas: census counts, shelter bed counts, records of transfer payments, and administrative agency estimates. We estimate similar statistical models using four different samples of data on the incidence of homelessness, defined according to very different criteria. Our results suggest that simple economic principles governing the availability and pricing of housing and the growth in demand for the lowest-quality housing explain a large portion of the variation in homelessness among U.S. metropolitan housing markets. Furthermore, rather modest improvements in the affordability of rental housing or its availability can substantially reduce the incidence of homelessness in the United States. 2000 by the President and Fellows of Harvard College and the Massachusetts Institute of Technology